Intravenous ibuprofen (IV-ibuprofen) controls fever effectively in adults with acute uncomplicated Plasmodium falciparum malaria but prolongs parasitemia. - Krudsood, S; Tangpukdee, N; Wilairatana, P; Pothipak, N; Duangdee, C; Warrell, D; Looareesuwan, S (2010)
Because some febrile patients are unable to swallow or retain oral antipyretic drugs, we carried out a double-blind, placebo-controlled trial in which intravenous ibuprofen (IV-ibuprofen) was given to adults hospitalized with fever associated with acute uncomplicated falciparum malaria treated with oral artesunate plus mefloquine. Thirty patients received IV-ibuprofen 400 mg and 30 received placebo every 6 hours for 72 hours. Reduction in the area above 37.0 degrees C versus time curve was significantly greater for IV-ibuprofen than for placebo during the first 72 hours after first administration. No patients developed severe malaria; parasite clearance was delayed in the patients whose fevers were controlled by IV-ibuprofen (median 37.3 hours versus 23.7 hours in the placebo group [P = 0.0024]). This difference did not appear to be clinically important Adverse events, none considered severe, occurred equally in both groups. IV-ibuprofen was effective and well tolerated in reducing fever in febrile inpatients with malaria.